Аggregated methodology for determining human resources needs of the road transport sector in the region with specialized education - N. N. Yakunin; O. U. Frolov; N. V. Yakunina; V. V. Kotov (Вестник СибАДИ)
Introduction. The existing methodology of personnel training determines the requirements for the competencies of future specialists, but the methods for determining the number of trained specialists are based either on the readiness of educational institutions for the quality management of the educational process, or are limited to the level of a motor transport enterprise, and do not take into account the regional needs of the labor market. The system of personnel training for the regional road transport complex is unbalanced in relation to the needs of this complex. This is due to the urgency of developing an enlarged methodology for determining the needs of the region’s motor transport complex (ATCR) in specialists with specialized education.Materials and methods. The paper uses the method of questioning economic entities engaged in road transport activities not only as the main focus, but also as an auxiliary one. The survey is aimed at determining the share of employees of motor transport enterprises and departments of various industries, taking into account the level of specialized education. The provisions of the theory of technical operation of cars and methods of mathematical statistics are used in the work.Results. The main result of the work is an enlarged methodology for determining the needs of the motor transport complex for specialists with specialized education, which differs from the known ones in that it takes into account the quantitative characteristics of personnel, taking into account the level of education in the economic entities of the region of various organizational and legal forms. These results represent the scientific novelty of the study. The structural characteristics of the personnel are determined, the corresponding algorithm is developed. The comparative values of labor productivity of specialists with specialized motor transport education are given.Discussion and conclusions. The methodological tools for determining the needs of the regional motor transport complex in specialists with specialized education have been developed, which allows overcoming the existing imbalance between the system of personnel training for the regional motor transport complex and the needs of this complex. The application of the results of the work will increase the validity of the state task for the training of specialists in the motor transport profile in the regions, increase the efficiency of using budget funds and public funds for educational activities.